Desain Sistem Pengapian Capacitor Discharge Ignition Menggunakan Proteus Berbasis Arduino Nano Untuk Meningkatkan Perfoma Sepeda Motor - Aqmal, Faril (CV. Sekawan Siji, 2025)
The traditional platinum ignition system produces lower combustion compared to the CDI ignition system. This is caused by the combustion chamber and air not mixing directly because the platinum components are mechanical and experience wear due to friction. Therefore, the development of a CDI ignition system based on the Arduino Nano microcontroller was implemented to achieve ignition stability and fuel consumption. The Arduino Nano microcontroller regulates ignition based on RPM to improve engine efficiency and performance. The test results show that measuring RPM with the Arduino Nano microcontroller regulates ignition timing in the RPM range of 0-15,000 RPM with a current of 6-8A and a voltage of 320-400V varying. The magnitude of the RPM causes a significant decrease in current and voltage, while the increase in RPM can be overcome by the addition of a digital filter. This Arduino-based CDI ignition system can produce larger sparks with efficient ignition timing at high RPM rotations.